Eksperimen Pembelajaran Matematika dengan Strategi Creative Problem Solving (CPS) Terhadap Pemahaman Konsep Ditinjau dari Kemampuan Komunikasi Matematis pada Siswa Kelas VIII SMP Muhammadiyah 7 Surakarta Tahun 2015/2016 - Sundari, Sri, Prof.Dr.Budi Murtiyasa, M.Kom (2016)
The ability to understand the concept is the most fundamental thing in mathematics and a prerequisite for mastering the material or the concept further. Require Creative Problem Solving (CPS) learning strategy to improve students' understanding of the concept. Besides mathematical communication ability also affects the students' understanding of the concepts. The research is conducted to know: (1) the effect of learning strategy to understanding of mathematic concepts, (2) the effect of mathematics communication ability to understanding of mathematic concepts, (3) interaction between learning strategy and mathematics communication ability to understanding of mathematic concepts. The research is a quasi-experimental research. The population of research is all of the 8th grades of Junior High School in Muhammadiyah 7 Surakarta in academic years of 2015/2016. There are two classes used as sampling is class VIIIC and VIIID. The technique of sampling is cluster random sampling. The technique of collection data are test, questionnaire, and documentation. Technique of analyzing data used analysis of variance two different cells. The research result show that: (1) there is effect of learning strategy to understanding of mathematic concepts i.e. Fobs=5.043162554>Fα=4.04, (2) there is effect of mathematics communication ability to understanding of mathematic concepts i.e. Fobs=4.961960009>Fα=3.19, (3) there is no interaction between learning strategy and mathematics communication ability to understanding of mathematic concepts i.e. Fobs = 0.062722434 < Fα = 3.19.